Meeting Across History: A Dialogue. Issue 2 (4th March 2019) - Frie, Roger; Grand, Sue
Abstract : In the coda, Frie and Grand mutually explore what facilitated their process of interaction and dialogue. Frie is the grandson of a Nazi party member, and Grand is the daughter of an American Jewish soldier who liberated Dachau. Through Frie's article and Grand's discussion, they worked together to find an I–Thou relation in the shadow of this history. Their interaction in the coda focuses on issues of historicity, ethical clarity, and moral responsibility. They explore our internalized perpetrator legacies—how these legacies live within us, and how we can know, contain, and repair these histories. They examine the prevalence of bystander cultures, past and present, and consider the importance of acknowledging and addressing the transmission of perpetrator histories.